2008
DOI: 10.1021/jp710461p
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive J-Aggregation Behavior of a Novel Azobenzene−Phthalocyanine Dyad and Its Third-Order Optical Nonlinearity

Abstract: The photoresponsive J-aggregation behaviors of a novel azobenzene-substituted zinc phthalocyanine (azo-ZnPc dyad) were studied by UV/vis, fluorescence, and (1)H NMR spectroscopy. Upon illumination with 365 nm UV light, the trans-cis isomerization of azobenzene can efficiently reduce the steric hindrance around the peripheral oxygen atom of azo-ZnPc, shortening the possible distance between two phthalocyanine molecules and, consequently, greatly improving the tendency of J-aggregation of azo-ZnPc dyad. The thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…In 2008, we reported the photo-responsive J-aggregation behavior of a novel -aryloxysubstituted zinc phthalocyanine (azobenzene substituted zinc phthalocyanine, hereafter, abbreviated as azo-ZnPc dyad) and its third-order optical nonlinearity (Chen et al, 2008). The azo-ZnPc dyad was synthesized through a rather facile route as shown in Scheme 1.…”
Section: Azobenzene-phthalocyanine Dyadsmentioning
confidence: 99%
“…In 2008, we reported the photo-responsive J-aggregation behavior of a novel -aryloxysubstituted zinc phthalocyanine (azobenzene substituted zinc phthalocyanine, hereafter, abbreviated as azo-ZnPc dyad) and its third-order optical nonlinearity (Chen et al, 2008). The azo-ZnPc dyad was synthesized through a rather facile route as shown in Scheme 1.…”
Section: Azobenzene-phthalocyanine Dyadsmentioning
confidence: 99%
“…The significant UV-Vis spectra changes in Figure 1(a) suggested that the J-aggregation of 3-azo-ZnPc could be effectively modulated by light in a large range. In our previous work [23] azobenzene moieties adopting cis configuration proved helpful to J-aggregation. In the current work, it was found that when azobenzene moieties in 3-azo-ZnPc were in trans conformation, only slight J-aggregation was seen.…”
Section: Resultsmentioning
confidence: 97%
“…Choosing azobenzene group as the substitution group in α-aryl/alkoxy-substituted zinc Pcs ( Figure 1) may result in novel Pcs whose J-aggregation degree could be modulated by light. This strategy has been testified by our recent work [23] , in which a symmetrical α-phenylazophenoxy-substituted zinc Pc (abbreviated as azo-Pc) was synthesized and investigated. It was found that J-aggregation of azo-Pc was significantly enhanced by light-induced trans-cis isomerization.…”
mentioning
confidence: 99%
“…They exhibit excellent photophysical property, architectural flexibility, diverse coordination properties and chemical and thermal stability [1]. Due to the synthetic flexibility with insertion of various metal ions in the inner core of Pc ring, synthetic chemists can able to rationally design the structure of Pc based on their needs [2][3][4]. The unique properties with increased stability of metallophthalocyanines (MPcs) made as a potential candidates in several fields such as catalysts [5,6], display devices [7], jet printing inks [8], solar cells [9][10][11], chemical sensors [12,13] data storage [14] and photonic devices [15].…”
Section: Introductionmentioning
confidence: 99%